Synthesis of α-tertiary amines by polysulfide anions photocatalysis via single-electron transfer and hydrogen atom transfer in relays - Li, Haoyu (2022)
α,α,α-Trisubstituted amines (α-tertiary amines) are an important class of compounds in drug discovery programs. Herein, we report a photocatalytic method to synthesize α-tertiary amines using polysulfide anions as photocatalysts that facilitate single-electron transfer (SET) and hydrogen atom transfer (HAT) in relays to enable α-C–H functionalization of α-secondary benzylamines with cyanoarenes or aryl ketones under irradiation with visible light. The keys enabling advance in the present protocol take advantage of highly negative photoexcited oxidation potential of polysulfide dianions (Sn2−, n = 4 or 6) to cover a range of cyanoarenes and aryl ketones for their SET reduction as well as the catenated structure of polysulfide anion radicals (Sn⋅–, n = 4 or 6) capable of polarity-driven HAT at the hindered α-amino benzylic C–H bond. Thus, ensuing coupling of cyanoarene radical anions or ketyl anion radicals with α-amino benzylic radicals allows for facile construction of sterically congested α-tertiary amine scaffolds.